Active Within Structures: Predictors of Esports Gameplay and Spectatorship. (April 2022) - Tang, Tang; Kucek, Jake; Toepfer, Steven
This study puts both esports gameplay and spectatorship into consideration and pinpoints how individual and structural factors explain why people play and watch esports to better understand the complexities and intricacies of esports consumption. Results indicate that both measures commonly associated with active audience, and structural theories played a significant role in explaining esports consumption. Specifically, esports gameplay was explained relatively more by structural factors than by individual factors. Different from esports gameplay, esports spectatorship was driven significantly more by individual factors. Preferences, motivations, availability, and access significantly predicted both esports gameplay and spectatorship. Sports fandom and use of interactive features, on the other hand, only predicted esports spectatorship but did not influence gameplay. By employing an integrative approach, this study aids in the development of conceptual framework that will serve to predict esports consumer behavior.